ANALISA KEKERASAN DAN STRUKTUR MIKRO PADA BAJA AISI 1018 AKIBAT PROSES PACK CARBURIZING DENGAN VARIASI KONSENTRASI SERBUK CANGKANG KEONG EMAS - Zainuri, Achmad; Setyawan, Paryanto Dwi; Atmam, Prayuda (Universitas Mataram, 2011)
This research to investigate the effect of Pomacea Canalikulata Lamarck powder addition in the process of carburization box to physical (microstructure) and mechanical properties (hardness test) of AISI 1018 after heat treatment. In this research used a material of low carbon steel cylinder (AISI 1018). The process of making the specimen is done with to cut into several pieces, cutting done to ease in placing the specimen in the carburizing box, then wood charcoal powder and shell powder were weighed in accordance with the desired composition by mixing powder of 5 wt%, 10 wt%, and 15 wt%. The specimen was done heat treatment at a temperature of 9500C with the holding time at 2, 4 and 6 hours. Then, the specimen was done the Vickers hardness test, microstructure and composition test. From this research it can be concluded that the highest hardness value was obtained at 15 wt% addition of shell powder it was 262.26 kg/mm2 and the initial material hardness value was 144.08 kg/mm2. From microstructure observation and composition test show that it subjected surface hardening because carbon diffusion into specimen.